1977
DOI: 10.1021/jf60212a052
|View full text |Cite
|
Sign up to set email alerts
|

Microwave conditioning of durum wheat. 1. Effects of wide power range on semolina and spaghetti quality

Abstract: Crosby durum wheat was conditioned with microwave energy at 2450 MHz before experimental milling and processing. Randomly selected duplicate samples were irradiated at 625 W up to 600 s, in 120-s increments. The temperature of conditioned samples ranged from 22 "C (0 s) to 110 "C (600 8 ) . Physicochemically important semolina and spaghetti quality parameters were adversely affected after 360 s (+25.9 cal/g) of microwave conditioning. Milling behavior and physical dough characteristics were reduced after prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…The total protein contents was not affected significantly (p<0.05) by heating with microwave treatment. The ranges of moisture value and protein content in samples are similar to the results obtained from previously studies (Doty and Baker 1977;Campaña et al, 1986Campaña et al, , 1993Lupano and Anón 1987;Türker and Elgün 1998;Walde et al, 2002;Vadimbal and Jayas 2007).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The total protein contents was not affected significantly (p<0.05) by heating with microwave treatment. The ranges of moisture value and protein content in samples are similar to the results obtained from previously studies (Doty and Baker 1977;Campaña et al, 1986Campaña et al, , 1993Lupano and Anón 1987;Türker and Elgün 1998;Walde et al, 2002;Vadimbal and Jayas 2007).…”
Section: Resultssupporting
confidence: 90%
“…This finding indicated that thermal denaturation of glutens in sound and damaged samples might be with different microwave times owing to having different levels of proteolytic activity in flours. The changes in WG content are similar to the findings previously reported by many authours (Doty and Baker 1977;MacArthur, 1981;Campaña et al, 1986Campaña et al, , 1993Lupano and Anón, 1987;Koksel et al, 1993;Türker and Elgün, 1998;Kaasov et al, 2002;Walde et al, 2002).…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations